Hubungan Antara Masa dan Lama Kerja Dengan Keluhan Nyeri Otot Skeletal (Musculoskeletal Disorders) - Darlis, Idhar; Elyanovianti (Jurnal Keolahragaan JUARA, 2023)
Musculoskeletal Disorders (MSDs) are a collection of symptoms or disorders related to muscle tissue, tendons, ligaments, cartilage, nervous system, bone structure, and blood vessels. MSDs initially cause aches, pains, numbness, tingling, swelling, stiffness, tremors, sleep disturbances and burning sensations. This study aims to determine the relationship between period and length of work with complaints of Musculoskeletal Disorders. The type of research used is quantitative research using a cross sectional approach. This research was carried out in Makassar City on student city transportation cooperatives and public route 05 Makassar City. The sampling technique uses purposive sampling. The analysis used was bivariate analysis using the chi-square test. The results showed that there was no relationship between length of work and Musculoskeletal Disorders. It is expected that public transport drivers for route 05 Makassar city will do stretching before and after work to stretch tense muscles and drink enough water in a day and rest should be done routinely every time they make 1 route round.